Do Well-Being and Job Motivation Impact Job Satisfaction? An Approach Based on Positive Emotions and Herzberg’s Two-Factor Theory - Susetyo, Aryo Ajie; Sukmawan, Krisma Ika; Sulistiyowati, Lisa Harry (Jurnal Ilmiah Akuntansi dan Keuangan, 2025)
Amidst the global labor shortage and high employee turnover, CV SN JAYA PRIMA, a wood manufacturing company, shows a different condition. Unlike the global trend, the company experiences low employee turnover, with a healthier, more productive and long-term committed workforce. This study investigates the relationship between well-being, work motivation and job satisfaction, using the PERMA model (Positive Emotions, Engagement, Relationships, Meaning and Achievement) and Herzberg's Two Factor Theory (hygiene and motivation factors). A quantitative approach is used in a case study of 225 employees of CV SN JAYA PRIMA. Regression analysis using SPSS shows that well-being and work motivation have a significant effect on job satisfaction. These results emphasize the importance of building well-being and motivation as an effort to improve job satisfaction and employee retention. The company's success provides insights for other industries in addressing workforce retention challenges.